REGULATORY DEVELOPMENTS IN SHARIA BANKING: IMPLICATIONS FOR THE DYNAMICS OF SHARIA BUSINESS UNIT SPIN-OFF IN INDONESIA - Muhammad Hakim Sitompul (Az-Zahra Media Society, 2025)
This research examines the impact of regulatory developments on the dynamics of Sharia Business Unit (SBU) spin-offs in Indonesia. The study aims to explore how regulatory frameworks, particularly Law No. 21 of 2008, influence the performance, compliance, and competitiveness of SBUs transitioning into independent Sharia Commercial Banks (SCBs). The scope of this research covers the financial, regulatory, and operational aspects of Islamic banking. A mixed-methods approach was employed, utilizing qualitative analysis of regulatory frameworks and quantitative financial data from various Sharia banks and SBUs. Data were sourced from financial reports and interviews with key stakeholders in the banking sector. The findings reveal that while spin-offs offer opportunities for SBUs to enhance market power and Sharia compliance, they also face challenges in governance and resource management. Notably, effective regulatory oversight and strategic management are crucial for long-term success. These results provide insights for policymakers and industry stakeholders on improving Islamic banking's competitiveness and sustainability.